Tourism Policy, a Big Push to Employment: Evidence from a Multiple Synthetic Control Approach - Victoria Castillo; Lucas Figal Garone; Alessandro Maffioli; Lina Salazar (Inter-American Development Bank (IDB), 2015)
This paper investigates the impact of tourism policy on employment, using the Tourism Development Policy (TDP) implemented in the Argentinean province of Salta during the years of 2003 to 2010 as a case study. Following the Synthetic Control Method for comparative case studies, we use a combination of non-treated Argentinean provinces to construct a synthetic control province which resembles relevant characteristics of Salta before the TDP implementation. Given the dual focus of the evaluated policy -one specific sector in one province- we also construct a synthetic control for the tourism sector using a combination of other sectors for Salta, and other sectors from other provinces. This novel approach based on multiple dimensions of the donor pool allows us to test the robustness of the estimated impact. We find that TDP implementation increased tourism employment in Salta by an average of 11 percent per year, for an overall impact of around 112 percent between 2003 and 2013. The analysis also suggests that larger impacts of the TDP occurred from the second to the seventh years after policy implementation. Results are robust across a series of placebo tests and sensitivity checks.
hdl:11319/6796
Keywords: E24; E65; H40; J49; L83; N56; 330; Tourism; employment; policy evaluation; synthetic control method; economic development; Argentina